PREFERENSI KONSUMEN TERHADAP PRODUK OLAHAN SAGU - Hasbi, Andi Rizkiyah; Sari, Harmita (Journal Galung Tropika, 2019)
The purpose of this study was to determine consumer preferences for processed sago products, by taking into account several attributes attached to the processed sago products. The study used a survey method using a questionnaire and was carried out in Palopo City, South Sulawesi. Sampling was carried out in three places which were the centers of marketing of sago products which were considered quite affordable by respondents, namely the Pusat Oleh-Oleh Palopo (Souvenir Center Palopo), Pusat Niaga Palopo (Commercial Center ), and the Toko Baru. The research data were processed using Chi-Square analysis to determine consumer preferences for processed sago purchase decisions. The results showed that the most considered attribute in the purchase of sago product was bagea cake with peanut-flavored at a price of Rp 15,000 – Rp 35,000, medium packaging, and easy to carry.